ORGANIZING COURSES IN PRE-SCHOOL EDUCATIONAL INSTITUTIONS - Sidiqova Yulduz Sobirovna (Researchparks Publishing, 2023)
In this article, the form of education, types of training in the organization of training in preschool educational institutions, A word about what should be paid attention to in organizing small children's life and nature around them, activities to develop their speech and the simplest mathematical ideas, music activities, building and making, physical education activities in MTM is carried out.